Determinants of Banking Sector Audit Report Lag: Evidence from Indonesia - Sudradjat Sudradjat; Jouzar Farouq Ishak; Arie Apriadi Nugraha (Jurnal ASET (Akuntansi Riset), 2023)
The main purpose – This study aims to examine the influence of audit committee characteristics, reputation of public accounting firms, and the COVID-19 crisis on the Audit Report Lag (ARL) of the banking sector in Indonesia..Method - This study uses annual panel data from 40 banks listed on the Indonesia Stock Exchange for the 2014-2021 period. The analytical method used in this study is the Random Effect Model.Main Findings – The results show that the frequency of audit committee meetings and the reputation of the public accounting firm have a negative effect on the ARL of the banking sector in Indonesia. Meanwhile, the COVID-19 crisis had a positive effect on the ARL of the banking sector in Indonesia. However, the research failed to prove the influence of the size of the audit committee and women's audit committee on the ARL of the banking sector in Indonesia.Theory and Policy Implications – This research contributes to the development of corporate governance literature on the relationship between the characteristics of audit committees and the reputation of public accounting firms and the ARL of the banking sector, in times of crisis such as the COVID-19 pandemic. This research adds insight for bank regulators, investors, and other business people about the factors that affect the ARL of the banking sector in Indonesia, which allows them to control the ARL more effectively.Novelty – This study is one of the first to consider women's audit committees, the reputation of public accountants, and the COVID-19 crisis in relation to the ARL of the banking sector, particularly in Indonesia. Keywords - Audit report lag, audit committee characteristics, public accounting firm reputation, COVID-19 crisis, Indonesian banking sector.